2020
DOI: 10.1002/mp.14436
|View full text |Cite
|
Sign up to set email alerts
|

Surface brachytherapy: Joint report of the AAPM and the GEC‐ESTRO Task Group No. 253

Abstract: The surface brachytherapy Task Group report number 253 discusses the common treatment modalities and applicators typically used to treat lesions on the body surface. Details of commissioning and calibration of the applicators and systems are discussed and examples are given for a risk-based analysis approach to the quality assurance measures that are necessary to consider when establishing a surface brachytherapy program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 89 publications
(258 reference statements)
1
17
0
Order By: Relevance
“…The two-year outcomes of our study are very encouraging and confirm the results of previous analyses reporting favorable outcomes after cHDR-RT of NMSC (16). More generally, ours and other reports show that cHDR-RT represents an effective and safe therapeutic option for NMSCs, as confirmed by their inclusion in several international guidelines published in recent years (17)(18). Moreover, some literature reviews confirmed that cHDR-RT is effective in NMSC treatment, with around 97% local control rate and 94.8% excellent or good cosmetic results even in elderly patients (19,20).…”
Section: Discussionsupporting
confidence: 90%
“…The two-year outcomes of our study are very encouraging and confirm the results of previous analyses reporting favorable outcomes after cHDR-RT of NMSC (16). More generally, ours and other reports show that cHDR-RT represents an effective and safe therapeutic option for NMSCs, as confirmed by their inclusion in several international guidelines published in recent years (17)(18). Moreover, some literature reviews confirmed that cHDR-RT is effective in NMSC treatment, with around 97% local control rate and 94.8% excellent or good cosmetic results even in elderly patients (19,20).…”
Section: Discussionsupporting
confidence: 90%
“…The source is a vacuum tube (10 mm in length, 2 mm in diameter) encased in a cooling catheter (5.6 mm diameter). It is typically operated at 50 kVp with 300 μA of electrons striking a thin tungsten film target on the inner surface of a ceramic X-ray-transparent anode ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Flexible, flap-like applicators are commercially available. These are a viable option for some large skin cases, due to consistent catheter spacing and flexibility as well as the ability to cut the flap to specific dimensions or affix it to other immobilization devices to improve reproducibility [23]. However, the flap applicators limit how close the sources can approach the skin and how well the flap geometry conforms to rapidly varying skin topology.…”
Section: Traditional Applicators -Benefits and Drawbacksmentioning
confidence: 99%
“…There is a growing interest in the development of AM applicators for skin BT. There is, however, a lack of review articles, and the latest guidance document from AAPM and GEC-ESTRO acknowledges that neither a standard of care nor comprehensive guideline exists yet for surface brachytherapy, let alone the inclusion of AM applicators [23].…”
Section: Clinical Need For Additive Manufacturing Applicatorsmentioning
confidence: 99%